Electrochemical Skin Conductance as a Marker of Painful Oxaliplatin-Induced Peripheral Neuropathy - Jean-Baptiste Delmotte; Abdulkarim Tutakhail; Kahina Abdallah; Pauline Reach; Marguerite D’Ussel; Gael Deplanque; Hélène Beaussier; François Coudoré (Neurology Research International)
Purpose. Oxaliplatin is a platinum compound widely used in gastrointestinal cancer treatment but produces dose-limiting peripheral neuropathy. New insights into oxaliplatin-induced peripheral neuropathy (OIPN) assessment are needed to detect more effectively this condition. In this context, we conducted Canaloxa study, a prospective preliminary clinical trial that aimed to investigate how Electrochemical Skin Conductance (ESC), a parameter used in small fiber neuropathy assessment, could be helpful in OIPN diagnosis. Methods. Cancer patients treated for at least three months with oxaliplatin and suffering from clinically OIPN were included. Electrochemical Skin Conductance, thermal thresholds, and neuropathic pain were assessed in all included patients. Results. During one year, 36 patients were included. The main result was the correlation between ESC and Neuropathic Pain Symptom Inventory score for hands (rho value = -0.69, p < 0.0001) and feet (rho value = -0.79, p < 0.0001). ESC values were lower in neuropathic patients with painful symptoms than in ones without painful symptoms (p = 0.0003 and p < 0.0001 for hands and feet, respectively). No correlation was observed between ESC and thermal thresholds. Conclusion. These preliminary data suggest that ESC could be a useful objective marker of painful oxaliplatin-induced neuropathy and could complement the use of subjective clinical scales. This study was prospectively registered on clinicaltrials.gov (NCT02827916) before patient recruitment has begun.